Effect of Nitrogen Rates and Leaf Clipping on Forage and Grain Yield, and Seed Quality of Transplant Aman Rice - Karmaker, Banani; Karmakar, Biswajit (Bangladesh Rice Journal, 2020)
Sustainable fodder production is difficult from limited cultivable land occupied for food grain production. This paper presents the results of the experiment designed to test the hypothesis that forage could be produced along rice grain from the same rice field. The aim of the present study was to investigate the influence of N-rates and leaf clipping on forage and grain yield; and seed quality of transplant Aman (wet season) rice. Four nitrogen (N) rates (N1=46, N2=69, N3=92 and N4=115 kg N ha-1) and four times of leaf clipping viz, C0=No leaf clipping, C1=leaf clipping at 25 DAT (Days after transplanting), C2=40 and C3=55 DAT were evaluated following split-plot design with three replications. BRRI dhan41 was used in the experiment. N rates, leaf clipping times and its interaction had significant effects on forage and grain yield, yield components and seed quality except thousand grain weight. The results revealed that forage yield increased with increasing N rates and leaf clipping times. Grain yield was higher in higher N rates and early leaf clippings, however, it was decreased in the late clipping (55 DAT). The highest mean grain yield (5.25 t ha-1) was obtained from the treatment combination of 115 kg N ha-1 (N4) and no leaf clipping (N4C0) which was statistically similar (5.18 t ha-1) to N3C0 (5.18 t ha-1), N3C1 (5.10 t ha-1) and N4C1 (5.06 t ha-1). The lowest mean grain yield (3.17 t ha-1) was obtained from N1C3. Grain yield was reduced by 3, 6 and 24% in C1, C2 and C3, respectively compared to C0 (No leaf clipping). Qualitative characters (germination and vigour index) of seed increased with increased N rates, however it decreased in the delayed leaf cuttings. Application of 92 to 115 kg N ha-1 with early leaf clipping (25 to 40 DAT) might be allowed to attain moderate forage yield, higher grain yield, and quality seed of transplant Aman rice. Bangladesh Rice j. 2019, 23(2): 49-57